Chemical Characteristics of Sea Grape (Caulerpa, sp.) Jam (Agrikan Jurnal Agribisnis Perikanan, 2022)
Sea grape â€œlatâ€ (Caulerpa, sp.) is a local food from Kei Island which used daily in the from of salads and has not been processed diversification. Example of diversification processed is a jam. The aim of this study was to indentify chemical characteristics of Caulerpa jam. The research method used is descriptive and proximate test. The result showed that the ratio of â€œlatâ€ is very influential on chemical characteristics of Caulerpa jam with ratio of â€œlatâ€ 3 : pineapple 1 has a better chemical composition to wit 30,39% water content, 3,12% ash content, 14,55% fat content, 1,39% protein contente and the carbohydrate contet by difference is 50,54%.
Keywords: Lat, Anggur Laut, Selai, Diversifikasi